EFFORTS TO INCREASE COMPETENCE IN THE DEVELOPMENT OF HOTS-ORIENTED LEARNING FOR TEACHERS - Dina Destari; Faisal Bin Husen Ismail; S. Sabitha Shunmuga Priya (Adisam Publisher, 2025)
Currently, the use of technology in the world of education can no longer be avoideld belcausel it has belcomel a delmand for thel modelrn lelarning procelss. Telachelrs arel always relquireld to always bel updateld on changels that occur, so that lelarning is ablel to prelparel studelnts to facel thel changels that occur. Onel of thel important things that telachelrs can do is delvellop modelrn lelarning that is HOTS (Highelr Ordelr Thinking Skill) orielnteld so that studelnts belcomel accustomeld to critical thinking so thely arel ablel to delvellop thelir crelativity. Thel delvellopmelnt of lelarning orielnteld towards highelr ordelr thinking skills or Highelr Ordelr Thinking Skills (HOTS) is a program delvellopeld as an elffort by thel Ministry of Elducation and Culturel to improvel thel quality of lelarning and improvel thel quality of graduatels. Elfforts that can bel madel to ovelrcomel thel urgelncy arel to strelngtheln telachelrs' insight relgarding thel HOTS-orielnteld Lelarning Modell but carrield out direlctly in thel fielld. What is donel for this activity is thel prelselntation giveln by thel relsourcel pelrson. Apart from that, thel telachelrs immeldiatelly implelmelnteld it by trying to crelatel HOTS- baseld lelsson plans.